Three water mite species of the genus Protzia Piersig (Acari: Hydrachnidia) from the Balkan, with the description of one new species - Pesic, Vladimir M. (Zootaxa, 2003)
Three water mite species of the genus Protzia Piersig are reported from Serbia and Montenegro, Bosnia and Herzegovina, and Bulgaria. Protzia durmitoris is described as new species. The first record from the Eastern Mediterranean region is given for Protzia halberti (Walter, 1920).